Medicines not recommended for inclusion in the who essential medicines list: a retrospective observational study - Costa, Enrico; Del Grosso, Vittorio; Cappello, Bernadette; Genazzani, Armando A.; Huttner, Benedikt; Leufkens, Hubert G. M.; Magrini, Nicola; Nonino, Francesco; Wirtz, Veronika J.; van den Ham, Hendrika A.; Moja, Lorenzo (Frontiers in Medicine, 2025)
BackgroundThe WHO Model List of Essential Medicines (EML) includes those medicines that offer the best health payback for individuals and health systems. It serves as a guide for countries to develop and update national EMLs. The implementation of essential medicines policies is therefore mostly oriented to medicines on the EML. However, medicines evaluated and not recommended for inclusion in the EML also have relevant implications for development of efficient medicine policies. This study analyzed the characteristics, frequencies, and reasons for applications for medicines proposed for inclusion in the WHO EML not being recommended.MethodsAssessment of the recommendations for all medicines proposed for inclusion in the WHO EML in reports of the Expert Committee on Selection and Use of Essential Medicines in the WHO Technical Reports Series from 2002 to 2023. We collected key information from EML applications including active substance, therapeutic indication, orphan status, applicant, and reasons for negative recommendations. Logistic univariate and multivariate regression analyses assessed predictive characteristics for applications with negative recommendations.ResultsA total of 359 applications for addition of new medicines to the EML were submitted: 211 (58.8%) received a positive recommendation. Among the 148 (41.2%) applications with a negative recommendation, the most prevalent reasons for not recommending were quality of clinical evidence (62.1%) and economic criteria (33.1%). Concerns about capacity to implement the new medicines in health care systems or requiring specialized expertise increased over time. Applications submitted by pharmaceutical companies, individuals not affiliated with scientific societies or non-governmental organizations, and academia were more prone to receiving a negative recommendation.DiscussionAn appreciable proportion of applications for addition of new medicines to the EML are not recommended. Over time, low or limited quality of clinical evidence was a consistent explanatory reason leading to non-recommending. Economic considerations and feasibility are emerging justifications for non-recommending.